Ti(C, N)-Based Cermets with Two Kinds of Core-Rim Structures Constructed by β-Co Microspheres - Hui Yan; Ying Deng; Yong Yao Su; Shan Jiang; Qiao Wang Chen; Shi Xiu Cao; Bing Liu (Advances in Materials Science and Engineering)
Ti(C, N)-based cermet materials represent the best choice of materials for the manufacturing industry and military products. In this study, we use cubic β-cobalt(β-Co) as the binder phase to strengthen constructed cermets. At the same time, to optimize the microstructure, (Ti, W, Mo, Ta) (C, N) powders are added to form two kinds of core-rim morphologies. Here, β-cobalt powders with face-centered cubic structures are obtained by the solid-phase reaction of high-energy ball milling. A solid-phase chemical reaction and a carbothermic reduction-nitridation method are used to prepare the (Ti, W, Mo, Ta) (C, N) powders. In our process, first we mix the cobalt and (Ti, W, Mo, Ta) (C, N) powders; then we press the powder mixtures into rectangular samples and sinter them in a pressure sintering furnace to obtain Ti(C, N)-based cermets with two kinds of core-rim structure, that is, black core/white rim and white core/gray rim. The results show that the new cermets demonstrate excellent toughness and performance.